Perlindungan Hukum Terhadap Perempuan dan Anak Korban Kejahatan Perdagangan Manusia - Iin Ratna Sumirat (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2017)
In Indonesia, the protection and the accolade towards human rights is still pathetic, in the reason that some cases on human rights violations such as coercion, discrimination, arbitrariness, etc often occur. Empirically, women and children are most vulnerable to become victims because of human trafficking. They are traded to be exploited and manipulated brutally as sexual objects, servitude, force labor, and so on. It must be paid attention by everyone in this country. This article would like to inform some of realities about it, and highlight the true meaning of human rights and its protection based on legislation and regulations of Indonesia constitution. It’s expected that the article becomes part of solutions for social problems related to women and children in Indonesia.